2016
DOI: 10.1111/jopr.12436
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Surface Roughness of Acrylic Resin Exposed to the Combined Hygiene Method of Brushing and Immersion in Ricinus communis and Sodium Hypochlorite

Abstract: The polished surface of the prosthesis was more susceptible to changes when exposed to hygiene solutions, and although the 0.5% NaOCl solution promoted an increase in the surface roughness compared with the same solution at 0.25% and R. communis at 10%, the values are clinically acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
1
23

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 34 publications
1
34
1
23
Order By: Relevance
“…The most commonly used chemical solution is NaClO, however it can cause deleterious effects to the denture when used at 1% or 0.5% concentrations 4 , 17 , 19 , 20 . Therefore, the assessment of NaClO at lower concentrations, as well as of new chemicals, is needed to help clinicians and patients find more suitable solutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most commonly used chemical solution is NaClO, however it can cause deleterious effects to the denture when used at 1% or 0.5% concentrations 4 , 17 , 19 , 20 . Therefore, the assessment of NaClO at lower concentrations, as well as of new chemicals, is needed to help clinicians and patients find more suitable solutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still necessary to evaluate the adverse effects of 0.25% NaClO and 10% R. communis (S3) on the acrylic resin of the denture. In the literature, only one study evaluated the surface roughness with the same solutions, which demonstrated clinically acceptable values, once they were below of 0.2 μm 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the useful life of these materials is compromised as a result of changes in physical integrity, surface detail, color, and fungal colonization . These changes can be intensified by the use of hygiene methods, which are essential for denture users, because they promote biofilm removal, assist in the control of oral diseases, and help maintain oral health.…”
mentioning
confidence: 99%